Evaluation of probiotic growth stimulation using prebiotic ingredients to optimize compounds for in ovo delivery - Akhavan, Niloofar; Hrynkiewicz, Katarzyna; Thiem, Dominika; Randazzo, Cinzia; Walsh, Ann M.; Guinan, Kieran J.; O’Sullivan, John T.; Stadnicka, Katarzyna (Frontiers in Microbiology, 2023)
The use of probiotics, prebiotics and synbiotics in poultry diets beneficially stimulates the gut microbiome thus promoting the health and welfare of the animals. In this study, we analyzed 7 poultry probiotics (Lactobacillus plantarum - B1 and B4, Lactobacillus rhamnosus – B3, Bifidobacterium lactis - B2, Carnobacterium divergens - B5, Propionibacterium thoenii - B6, Clostridium butyricum – B7) and 12 prebiotics, differing in chemical composition and source of origin (fungi, algae, animal, etc.). The main goal of our research was to select the most promising candidates to develop synbiotic combinations. We determined the growth kinetics of all probiotics in the presence of prebiotics in a series of in vitro studies to select optimal combinations. Five out of seven investigated probiotics were significantly stimulated by astragalus polysaccharide, and this prebiotic was characterized in our work as the most effective. Moreover, in the case of three probiotics, B2, B3 and B4, significant growth stimulation has been found when beta-glucan, vegetable protein hydrolysate and liquid seaweed extract were supplied. Strain B1 (L. plantarum) was stimulated by 6 out of 12 prebiotics. The growth of B4 (L. plantarum) and B2 (B. lactis) was enhanced by prebiotics after 2 hours of incubation. A high growth rate of 3.13% was observed in the case of L. plantarum (B4) and a 3.37% higher rate for B. lactis (B3), compared to the growth of probiotics in the control medium with glucose but no prebiotics. The best candidates for synbiotic combinations based on this in vitro work are the strains belonging to L. plantarum (B4), L. rhamnosus (B3) and B. lactis (B2), consistent with prebiotics such as astragalus polysaccharides and vegetable protein hydrolysate. These combinations will be subject to future in vivo poultry trials involving the in ovo microbiome modulation.